ACCEPTANCE OF THE INHERITANCE IN THE NEW CIVIL CODE REGULATION - ILIOARA GENOIU (Challenges of the Knowledge Society, 2011)
The new regulation in civil matter, represented by Law no. 287/2009 regarding the Civil Code, whose date to entry in force has not been established yet, reconfigures quasi-totally the acceptance inheritance institution. In this paper we will analyze the acceptance of the inheritance issue under all its aspects, as a valence of the successional option right, in the light of the new Civil Code dispositions. We will thus be able to reveal the novelties brought by the new regulation and to appreciate its progressive nature. In the acceptance of the inheritance matter, the new Civil Code innovates, mainly as regards its forms (in the new Civil Code the acceptance under benefit of inventory is no more regulated), the effects of the acceptance (the heirs are responsible for the debts and for the delivers of the inheritance only with the assets from the successional patrimony) and the procedure that has to be performed in the case of inventory preparation and taking special measures for preserving the successional assets. We hope that through our approach, we enrol in the overall effort to make known and understood the disposition of the new Civil Code, until its entry in force.